Shakespeare and his stage approaches to Hamlet - Seltzer, Daniel; Mantell, Harold (The History of the drama / produced by Harold Mantell, 1975)
A young actor's attempts to master the role of Hamlet are intercut with footage of the four greatest Hamlets of this century: John Barrymore, Lawrence Olivier, John Gielgud and Nicol Williamson.